PENGARUH KONSENTRASI GARAM TERHADAP KADAR PROTEIN DAN KUALITAS ORGANOLEPTIK TELUR PUYUH ASIN - Marni, Gusti; Amri, Erismar; Wati, Meliya (Pendidikan Biologi, 2014)
ABSTRACTÂ Quill eggs are food materials that have many potential because it is very helpful to supple nutrition for societies, especially to supple animals protein. One way of conservations is used salting preservation because it can hamper and kills bacteria in eggs. Due to have been done the research to know the influence of Salt Concentration on protein content and Organoleptic Quality Salted Quail Eggs. This research was conducted at the Regional Sicincin, Pariaman at September 2013 and determines the protein content ofÂ  saltedÂ  quail eggs doneÂ  inÂ  the Laboratory ofÂ  IntegratedÂ  Koperties X Padang. Â The purpose of this research is to know the influence of salt concentration on protein content and organoleptic quality in salted quail eggs. This research used a completely randomize design (RAL) with 5 treatments and 5 replications. Such treatment A (without salt), B (salt 2%), C (salt 4%) and E (salt 8%) were performed for three days. The result shows that the treatment with various concentrations 8% higher protein content compared to other salt concentration. In the organoleptic test with different concentrations of salt texture and aroma values of salt quails eggs obtained results were not significant. Value salty scent of quailâs eggs is highest at 8% concentration of salt and salt quailâs eggs texture values are highest in concentration 2%, while the value of the flavor and color of the salt quail eggs are highly significant. Color values salt quail eggs contained the highest concentration of salt in 8% and the value of quail eggs taste salty at the highest salt concentration 4%.